Komodifikasi Budaya Digital, Manipulasi Psikopolitik, dan Kolonialisme Data: Analisis Wacana Kritis Film The Great Hack (2019) - Pahlewi, Mhd. Reza; Pawito, Pawito; Hastjarjo, Sri (Universitas Muhammdiyah Yogyakarta, 2025)
The phenomenon of using personal data as a digital commodity raises serious issues related to privacy, ethics, and global democracy. The documentary film The Great Hack (2019) portrays the Cambridge Analytica scandal, which revealed how the data of millions of Facebook users were collected and exploited for political purposes. This study aims to analyze the representation of digital cultural commodification in the film by employing the theories of Cultural Commodification and Surveillance Capitalism. The research method applied is a qualitative case study through Norman Fairclough’s Critical Discourse Analysis, which encompasses the dimensions of text, discourse practice, and social practice. The findings indicate that personal data are treated as strategic economic assets, processed into psychographic profiles, and utilized to influence voter behavior in a segmented manner. Digital commodification differs from traditional forms as it operates algorithmically, on a massive scale, and often without the awareness of users. The study concludes that such practices not only violate individual privacy but also threaten the legitimacy of democracy and highlight the dominance of technology corporations in global communication.